Jysk Ordbog – Rapport fra en digital ordbog - Schoonderbeek Hansen, Inger (Nordiske Studier i Leksikografi, 2007)
The Peter Skautrup Centre has been publishing the Dictionary of Jutland Dialects (Jysk Ordbog) on the internet since October 2000, and everyone with access to a computer connecting the internet has free access to all articles from A to Hæ-. The multilayered site contains links to dialect geographical maps, references to applied literature, a list of editorial abbreviations, an overview of phonetical signs, and furthermore links to information on the editorial background of the dictionary, i.e. geographical distribution and the assembling of the large and varied material. As the process of editing is very complex and, more important, in a way hazardous due to out of date software, plans are being made to update the technical platform of the dictionary. This new, far more coherent platform will consist of first of all an editorial (webbased) database, written in a XML standard. As the Centre has succeeded in finding some of the acquired financing funds, the final phase will start in securing and making more easely available the online dictionary.